1981
DOI: 10.2355/isijinternational1966.21.250
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus distribution between liquid iron and MgO saturated slags of the system CaO-MgO-FeOx-SiO2.

Abstract: SynopsisExperiments have been made to study the phosphorus distribution between liquid iron and the Ca0-Si02 FeOx slag equilibrated in a magnesia crucible in the temperature range 1550° to 1650°C.The phosphorus distribution ratio (P205)/[P] increased with increasing Ca0 content and decreasing temperature. The maximum value of the distribution ratio was found to be present near the slag composition saturated with the tricalcium silicate and the magnesio wustite phases. The experimentally determined phosphorus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
151
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(164 citation statements)
references
References 1 publication
7
151
0
1
Order By: Relevance
“…The results 8) offers the best agreement while that of Turkdogan 9) shows slightly more scatter. However, the results differ from the values calculated through Eq.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…The results 8) offers the best agreement while that of Turkdogan 9) shows slightly more scatter. However, the results differ from the values calculated through Eq.…”
Section: Introductionsupporting
confidence: 56%
“…The ranges of CaO concentrations in the data used by the authors, 1,2) Suito et al 8) and Turkdogan and Pearson Similarly, the ranges of FeO concentrations in the data used by Suito et al 8) and Turkdogan and Pearson 3) varied as N FeO ϭ0.2-0.29 and 0.11-0.22, respectively. On the other hand, the range of FeO concentrations in the work of the present authors 1,2) was N FeO ϭ0.05-0.36 (X Fe 2ϩϭ0.07-0.42).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…slags at 1 823 K increases and is followed by a constant value within some experimental scatters. 5,6) However, the phosphate capacity of the Na 2 O-SiO 2 -Fe t O-5(Ϯ1)mass%MnO-MgO satd. system, which can be considered to be more basic than lime-based slags, linearly increases with increasing basicity index at 1 873 K. 8) Based on a definition of phosphate capacity given in Eq.…”
Section: ϫ6mentioning
confidence: 99%
“…The phosphate capacity of various MgO-saturated slags measured by several authors was also shown for comparison. [5][6][7][8][9][10][11][12] Here, the phosphate capacity of the slag was calculated from Eqs. (2) and (4).…”
Section: ϫ6mentioning
confidence: 99%